Factors Affecting Consumer Decision in Buying Herbalife Product During Covid-19 Pandemic - Dhaifina Idznitia Apriyani Naimi; Nurzahroh Lailyah; Keke Tamara Fahira (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The obesity rate in the last three years in Semarang City has increased, and the need for vitamins and nutrients during the Covid-19 pandemic has also increased. However, this fact is not in line with the number of requests for purchasing Herbalife products which has decreased. This study aims to analyze the factors influencing consumer decisions in buying herbalife products in Semarang. The sampling technique used purposive sampling. Data were obtained using a questionnaire distributed to 100 respondents. Consumer data were analyzed using a multiple linear regression model. The study’s results stated that the variables of price, place, and physical evidence significantly influenced consumers’ decisions to buy Herbalife products. In contrast, product, promotion, people, and process variables did not considerably influence consumer decisions in buying Herbalife products.